INTERNALISASI NILAI-NILAI ETNOPEDAGOGI MELALUI TRADISI SEBA BADUY PADA GENERASI MUDA - Adang Sutarman; Ujang Jamaludin Jamaludin; Asep Muhyidin; Aan Aspianto (Jurnal Ilmiah Pendidikan dan Keislaman, 2026)
This study aims to analyze the process of internalizing ethnopedagogical values through the Seba Baduy tradition among the younger generation and to examine its relevance in strengthening character education based on local wisdom. The Seba Baduy tradition is a cultural heritage of the Baduy indigenous community that embodies moral, social, spiritual, and ecological values and serves as a non-formal educational medium for young people. This study employed a qualitative descriptive approach. Data were collected through observation, in-depth interviews, and documentation involving traditional leaders, youth, and educators in the Baduy community of Lebak Regency, Banten Province, Indonesia. Data analysis was conducted through data reduction, data display, and conclusion drawing, supported by source and technique triangulation to ensure data validity. The findings reveal that the Seba Baduy tradition contains significant ethnopedagogical values, including simplicity, honesty, adherence to customary laws, mutual cooperation, social solidarity, spirituality, and harmony with nature. The internalization process occurs through role modeling by traditional leaders, active participation of youth in cultural rituals, social interactions within the community, and habituation in everyday life. Supporting factors include the role of family, strong social cohesion within the indigenous community, and the continuity of cultural traditions. Meanwhile, inhibiting factors arise from globalization, modernization, digital media influences, and the limited integration of local cultural values into formal education. The study concludes that the Seba Baduy tradition serves as a strategic source of ethnopedagogy that effectively contributes to character formation and strengthens cultural identity among the younger generation. Therefore, collaboration among schools, indigenous communities, and government institutions is essential to integrate ethnopedagogical values into the education system in a contextual and sustainable manner.